Analysis of the Application of The Siks-ng Application at The Gunung Gabungan Village Office, Gomo Sub-District South Nias District - Haezer Zebua, Eben; Ndraha, Ayler Beniah; Lase, Delipiter; Harefa, Peringatan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this research is to analyze the application of the Next Generation Social Welfare Information System (SIKS-NG) in Gunung Gabungan Village, Gomo Sub-district, South Nias Regency, and identify the obstacles faced in its use. The research method used is qualitative, with data collection techniques through observation, interviews, library research, and documentation. This research involved village officials and users of the SIKS-NG application as key informants. The results showed that although the SIKS-NG application has the potential to improve the efficiency of community data management, various obstacles such as the lack of understanding of village officials, limited infrastructure, and human resource capacity issues hinder the optimization of application use. Direct observations and interviews with informants revealed that intensive training and improved technological infrastructure are needed to support the implementation of this application. Further discussion shows the importance of collaboration between central and local governments as well as support from educational institutions in developing the capacity of village officials. This study concludes that the implementation of SIKS-NG in Gunung Gabungan Village requires a systematic and sustainable approach to overcome various obstacles, as well as to ensure the sustainability and effectiveness of the application in improving public services. Recommendations are given for the development of more comprehensive training and improved infrastructure to support optimal use of the application.